The Transformation of Higher Education After the COVID Disruption: Emerging Challenges in an Online Learning Scenario - García-Morales, Víctor J.; Garrido-Moreno, Aurora; Martín-Rojas, Rodrigo (Frontiers in Psychology, 2021)
Crisis requires society to renew itself, albeit in a disruptive way. The current Covid-19 pandemic is transforming our ways of working, living, and relating to each other at a global level, suddenly and dramatically. This paper focuses on the field of education to show how higher education institutions are undergoing a radical transformation driven by the need to digitalize education and training processes in record time, with academics who lack innate technological capabilities for online teaching. The university system must strive to overcome this situation to be competitive and provide high-quality education in a scenario of digital transformation, disruptive technological innovations, and accelerated change. To achieve these goals, this paper explains some barriers and challenges that universities encounter, as well as technological resources and methodologies they have used in the current scenario to transform higher education to face Covid-19 disruption. The discussion and conclusion synthesize significant insights that can be applied to the digitalization of education in the foreseeable future.